A method for preparing a soft magnetic core for a car charging pile

By adopting high-purity raw materials and advanced process technologies, such as high-pressure pressing, vacuum sintering, mechanical grinding and chemical polishing, combined with the use of nano-scale conductive particles and composite particle balls, the problem of unstable magnetic performance of existing soft magnetic cores for automotive charging piles under high frequency and high temperature conditions has been solved, significantly improving the performance and reliability of the magnetic core, and meeting the high requirements for magnetic cores of automotive charging piles.

CN118824717BActive Publication Date: 2025-04-01SHUYANG KANGSHUN MAGNETIC COMPONENTS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410986773.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-23
Publication Date
2025-04-01
Estimated Expiration
2044-07-23

AI Technical Summary

Technical Problem

The magnetic performance of existing soft magnetic cores for automotive charging piles is unstable under high frequency and high temperature conditions. The impact of impurities leads to deterioration of magnetic properties, complex processing technology and high cost, insufficient mechanical strength affects service life, thermal stress leads to cracks and deformation of the magnetic core, low surface finish and dimensional accuracy affect application performance, poor environmental adaptability leads to deterioration of performance in harsh environments, and imperfect detection standards make it difficult to comprehensively evaluate performance and quality.

Method used

High-purity iron powder, nickel powder, cobalt powder and rare earth elements are used as raw materials, and raw materials are mixed by combining mechanical stirring and ultrasonic stirring, and nano-scale conductive particles are added. The magnetic core is prepared by high-pressure pressing and vacuum sintering. Combined with mechanical grinding and chemical polishing, graded cooling and magnetic performance detection are performed. Finally, protective film and composite particle balls are coated on the outer end of the magnetic core to improve corrosion resistance and thermal stability.

Benefits of technology

It significantly improves the high-temperature stability, oxidation resistance and environmental adaptability of the magnetic core, enhances the density and structural uniformity of the magnetic core, improves the surface finish and dimensional accuracy, ensures that the magnetic core meets the requirements of automotive charging piles, extends the service life of the magnetic core, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118824717B_ABST
    Figure CN118824717B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a soft magnetic core for an automobile charging pile. The invention adopts high-purity iron powder, nickel powder, cobalt powder and rare earth elements, and adds nano-scale conductive particles to ensure high magnetic permeability, low coercive force and high-temperature stability. Mechanical and ultrasonic stirring are used to ensure powder uniformity and improve the density of the magnetic core. Cold isostatic pressing technology is used to make the magnetic core evenly stressed and enhance its mechanical strength and magnetic properties. Vacuum sintering and the addition of a hydrogen reducing atmosphere reduce the influence of impurities and enhance purity and magnetic properties. Gradual cooling avoids thermal stress and enhances stability. Mechanical grinding and chemical polishing enhance surface finish and dimensional accuracy. Comprehensive testing ensures that the magnetic core meets use requirements. A protective film adopts aluminum oxide and silicon nitride materials to prevent corrosion and extend service life. Composite particle balls are used to enhance thermal stability and resistance to heat loss. The overall process is simple and easy, which is conducive to large-scale production and cost reduction, and significantly improves the performance and service life of the charging pile.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of magnetic materials, and more specifically, to a method for preparing a soft magnetic core for a car charging pile. Background Art

[0002] Car charging piles usually use soft magnetic cores as the core material of the transformer. These cores need to have high magnetic permeability, low hysteresis, low loss and good thermal stability to ensure efficient energy conversion and stable operation. Soft magnetic cores for car charging piles are a key magnetic component used in electric vehicle charging equipment, mainly used in converters and inductors. The main function of these cores is to improve the efficiency of power conversion and reduce energy loss, thereby achieving efficient and fast charging of electric vehicles. Soft magnetic cores can easily lose their magnetism after being magnetized, which makes them particularly suitable for applications with frequently changing magnetic fields, such as in power conversion and regulation of charging piles.

[0003] In electric vehicle charging piles, soft magnetic cores play a vital role, mainly for energy conversion and current stabilization. These cores effectively improve energy conversion efficiency with high magnetic permeability and low loss characteristics by converting alternating current (AC) to direct current (DC) in the converter, and vice versa. At the same time, they are also used in inductors and filters to help smooth the output current, reduce voltage fluctuations and noise, and ensure the current supply of electric vehicles is stable and safe. Material options for soft magnetic cores include high permeability and economical silicon steel sheets, low hysteresis loss Permalloy, and high-efficiency iron-based nanocrystalline materials, which are suitable for high-frequency applications. Common core shapes such as toroidal, E-type and U-type are not only easy to manufacture and assemble, but also help to concentrate the magnetic field and improve overall performance and efficiency. The design and material selection of these components are critical to achieving efficient and reliable charging solutions.

[0004] The existing core materials have unstable magnetic properties under high frequency and high temperature conditions, impurities cause magnetic properties to decline, the processing technology is complex and costly, insufficient mechanical strength affects service life, thermal stress causes the core to crack and deform easily, surface finish and dimensional accuracy are not high and affect application performance, poor environmental adaptability leads to performance degradation in harsh environments, and incomplete testing standards make it difficult to fully evaluate performance and quality. These problems urgently need to be solved by improving material purity, optimizing production processes, improving mechanical strength and environmental adaptability, and improving testing standards to improve the performance and reliability of soft magnetic cores and meet the high requirements of automotive charging piles for core materials.

[0005] Therefore, in view of the above technical problems, it is necessary to provide a method for preparing a soft magnetic core for a car charging pile. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing a soft magnetic core for a car charging pile to solve the above-mentioned problems.

[0007] In order to achieve the above purpose, the technical solution provided by an embodiment of the present invention is as follows:

[0008] A method for preparing a soft magnetic core for a car charging pile comprises the following steps:

[0009] S1. Select high-purity iron powder, nickel powder, cobalt powder, and a small amount of rare earth elements as raw materials;

[0010] S2, mixing the raw materials selected in step S1 uniformly according to proportion and adding nano-scale conductive particles to obtain a mixed powder;

[0011] S3, placing the mixed powder in a mold and pressing it under high pressure to obtain a magnetic core of a preliminary shape;

[0012] S4, sintering the pressed magnetic core in a high temperature furnace and adding a hydrogen reducing atmosphere, and the sintered magnetic core is naturally cooled to room temperature;

[0013] S5, mechanically grinding and chemically polishing the cooled magnetic core to obtain a magnetic core of a desired size and shape;

[0014] S6. Conducting magnetic property testing on the prepared magnetic core;

[0015] By adding rare earth elements and nano-scale conductive particles, the high-temperature stability, antioxidant performance and environmental adaptability of the magnetic core are improved. High-pressure pressing and cold isostatic pressing technology ensure the density and uniformity of the magnetic core. The high-temperature sintering process in a hydrogen reducing atmosphere reduces the influence of impurities. Mechanical grinding and chemical polishing improve the surface finish and dimensional accuracy. Comprehensive magnetic performance testing ensures that the magnetic core meets the use requirements. The overall process is simple and easy, which is conducive to large-scale production and cost reduction.

[0016] As a further improvement of the present invention, the raw material ratio in step S1 is 65-75wt% iron powder, 10-15wt% nickel powder, 5-10wt% cobalt powder, and 1-5wt% rare earth element. The reasonable raw material ratio ensures the high magnetic permeability and low coercive force of the magnetic core, while increasing the high temperature stability and antioxidant properties of the magnetic core.

[0017] As a further improvement of the present invention, the raw material mixing in step S2 adopts a combination of mechanical stirring and ultrasonic stirring, and the particle size of the mixed powder is 1-10 microns. The combination of mechanical stirring and ultrasonic stirring ensures the uniformity of the powder, and the micron-level particle size helps to improve the density and uniformity of the magnetic core.

[0018] As a further improvement of the present invention, the pressing and forming in step S3 adopts cold isostatic pressing technology, and the cold isostatic pressing technology specifically includes:

[0019] S301, first, select appropriate high-purity powder materials, and mix and pre-treat them;

[0020] S302, loading the pretreated powder into a flexible mold;

[0021] S303, placing the mold filled with powder into a high-pressure container, and the high-pressure container is filled with fluid;

[0022] S304, gradually increasing the pressure of the fluid in the container to 200 MPa by means of a pump or other pressurizing equipment;

[0023] S305, after reaching the required pressure, maintain it for 30 minutes;

[0024] S306, after the pressing is completed, gradually reduce the pressure in the container until it returns to normal pressure, then remove the mold from the pressure container, carefully dismantle the mold, and take out the pressed blank;

[0025] S307, the pressed blank is further sintered;

[0026] Cold isostatic pressing technology allows the magnetic core to be evenly stressed during the pressing process, significantly improving the density and structural uniformity of the magnetic core.

[0027] As a further improvement of the present invention, the sintering in step S4 adopts vacuum sintering, and the temperature is controlled at 800°C-1200°C for 2-4 hours. Vacuum sintering reduces the influence of impurities and improves the purity and magnetic properties of the magnetic core; strict temperature and time control ensures the stability and consistency of the sintering process.

[0028] As a further improvement of the present invention, the cooling in step S5 adopts a graded cooling technology and controls the cooling rate, and the graded cooling technology specifically includes:

[0029] S501, after sintering is completed, the material is in a high temperature state;

[0030] S502, after reaching the initial cooling temperature of 600°C, maintaining the material at this constant temperature for 1 hour;

[0031] S503, after the isothermal holding stage, starting to gradually reduce the temperature, by controlling the temperature of the cooling medium and the temperature of the cooling chamber, slowly reducing the temperature at a rate of 10°C / min;

[0032] S504, after the slow cooling stage, the material temperature is further reduced to close to the ambient temperature, and this stage is completed by natural cooling and air cooling;

[0033] The cooling method of first fast and then slow can effectively avoid the influence of thermal stress on the performance of the magnetic core, further reduce the internal stress, and improve the stability and reliability of the magnetic core.

[0034] As a further improvement of the present invention, the performance test in step S6 includes the detection of magnetic permeability, coercive force, saturation magnetic flux density, and temperature stability parameters. Comprehensive performance testing ensures that various parameters of the magnetic core meet the use requirements of the automobile charging pile, ensures the quality and consistency of the magnetic core, and improves the performance and efficiency of the charging pile.

[0035] As a further improvement of the present invention, the outer end of the soft magnetic core is coated with a protective film, which is made of any one of aluminum oxide and silicon nitride. The protective film can effectively isolate the external environment, prevent moisture and oxygen from corroding the core material, and improve its corrosion resistance.

[0036] As a further improvement of the present invention, a plurality of uniformly separated composite particle balls are fixedly connected to the outer end of the protective film, and the composite particle balls include a wrapping ball film, which is fixedly connected to the outer end of the protective film, and is filled with a softening and solidifying glue. The softening and solidifying glue is doped with thermal insulation particles in the middle. The composite particle balls can effectively isolate heat and enhance the thermal stability of the magnetic core. The wrapping ball film is made of wax material, the softening and solidifying glue is made of thermoplastic polyurethane material, and the thermal insulation particles are made of aerogel material. Through the ingenious combination of these materials, the composite particle balls can soften and adhere when heated, thereby improving the thermal stability and heat loss resistance of the magnetic core.

[0037] As a further improvement of the present invention, the method for preparing the composite particle ball comprises the following steps:

[0038] ①. Use hot-melt material to make the ball membrane and reserve the injection hole;

[0039] ②, evenly mix the softened solidified glue and the heat-insulating particles, inject them into the wrapped ball membrane and seal the holes to obtain a composite particle ball;

[0040] ③. Sprinkle the obtained composite particle balls evenly on the surface of the coating protective film before it solidifies.

[0041] Compared with the prior art, the advantages of the present invention are:

[0042] This solution uses high-purity iron powder, nickel powder, cobalt powder and rare earth elements to ensure high magnetic permeability and low coercivity of the magnetic core, and greatly improves the high-temperature stability and antioxidant properties of the magnetic core. Nano-scale conductive particles are added during the raw material mixing process to further optimize the electromagnetic properties of the magnetic core and improve the conductivity and environmental adaptability of the magnetic core. A combination of mechanical stirring and ultrasonic stirring is used to ensure the uniformity of the mixed powder and control the powder particle size to microns, which helps to improve the density and uniformity of the magnetic core, thereby optimizing the magnetic properties.

[0043] This solution adopts cold isostatic pressing technology, so that the magnetic core is evenly stressed during the pressing process, which significantly improves the density and structural uniformity of the magnetic core, and enhances its mechanical strength and magnetic properties. A hydrogen reducing atmosphere is added during the vacuum sintering process to reduce the impact of impurities, improve the purity and magnetic properties of the magnetic core, and ensure the stability and consistency of the sintering process. The graded cooling technology is adopted and the cooling rate is controlled. The cooling method of first fast and then slow is used to effectively avoid the impact of thermal stress on the performance of the magnetic core, further reduce internal stress, and improve the stability of the magnetic core. The surface finish and dimensional accuracy of the magnetic core are improved through mechanical grinding and chemical polishing to ensure that the final shape and size of the magnetic core meet the requirements. A comprehensive test of magnetic permeability, coercive force, saturation flux density and temperature stability parameters is carried out to ensure that the magnetic core meets the use requirements of the car charging pile and ensure product quality and consistency.

[0044] This solution uses plasma spraying and chemical vapor deposition technology to coat the outer end of the magnetic core with a protective film of aluminum oxide and silicon nitride materials, which effectively isolates the external environment, prevents moisture and oxygen from corroding the magnetic core material, improves its corrosion resistance, and extends the service life of the magnetic core. A plurality of composite particle balls are fixedly connected to the outer end of the protective film. The composite particle balls are composed of a wrapping ball film, a softening and solidifying glue, and thermal insulation particles, which can effectively isolate heat and enhance the thermal stability of the magnetic core. The wrapping ball film is made of wax material, the softening and solidifying glue is made of thermoplastic polyurethane material, and the thermal insulation particles are made of aerogel material. Through the clever combination of these materials, the composite particle balls can soften and adhere when heated, thereby improving the thermal stability and heat loss resistance of the magnetic core. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a schematic diagram of the preparation method of the present invention;

[0046] Figure 2 It is a schematic diagram of the structure of the soft magnetic core of the present invention;

[0047] Figure 3 It is a schematic diagram of the cross-sectional structure of the composite particle ball of the present invention;

[0048] Figure 4 It is a schematic diagram of the preparation process of the composite particle ball of the present invention;

[0049] Figure 5 This is a specific experimental data table of the present invention.

[0050] Description of the numbers in the figure:

[0051] 1. Wrap the ball film; 2. Soften the solidified glue; 3. Heat insulation particles. DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention; it is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments, and all other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making creative work are within the scope of protection of the present invention.

[0053] Embodiment 1:

[0054] See also Figure 1 , a method for preparing a soft magnetic core for a car charging pile, comprising the following steps:

[0055] S1. Select high-purity iron powder 70wt%, nickel powder 12wt%, cobalt powder 8wt%, and rare earth element 2wt% as raw materials;

[0056] S2, the raw materials selected in step S1 are mixed evenly according to proportion and nano-scale conductive particles are added, and mechanical stirring and ultrasonic stirring are combined to obtain a mixed powder with a particle size of 5 microns;

[0057] S3, placing the mixed powder in a flexible mold, pressing and molding by cold isostatic pressing technology, and uniformly pressurizing the fluid in the high-pressure container to obtain a magnetic core of a preliminary shape;

[0058] S4, sintering the pressed magnetic core in a high temperature furnace and adding a hydrogen reducing atmosphere, vacuum sintering at a temperature of 900°C for 3 hours, and naturally cooling the sintered magnetic core to room temperature;

[0059] S5. The cooled magnetic core is processed by mechanical grinding and chemical polishing, and a graded cooling technology is used, including initial cooling, isothermal holding, slow cooling, and final cooling, to obtain a magnetic core of a desired size and shape;

[0060] S6. Conduct magnetic property testing on the prepared magnetic core, including magnetic permeability, coercive force, saturation magnetic flux density and temperature stability parameters;

[0061] By adding rare earth elements and nano-scale conductive particles, the high-temperature stability, antioxidant performance and environmental adaptability of the magnetic core are improved. High-pressure pressing and cold isostatic pressing technology ensure the density and uniformity of the magnetic core. The high-temperature sintering process in a hydrogen reducing atmosphere reduces the influence of impurities. Mechanical grinding and chemical polishing improve the surface finish and dimensional accuracy. Comprehensive magnetic performance testing is used to ensure that the magnetic core meets the use requirements. The overall process is simple and easy, which is conducive to large-scale production and cost reduction, thereby significantly improving the performance and efficiency of the charging pile and extending its service life.

[0062] In step S1, the raw material ratio is 65-75wt% iron powder, 10-15wt% nickel powder, 5-10wt% cobalt powder, and 1-5wt% rare earth element. The high magnetic permeability and low coercive force of the magnetic core are ensured through reasonable raw material ratio, while the high temperature stability and oxidation resistance of the magnetic core are increased, thereby improving the environmental adaptability of the magnetic core in the car charging pile.

[0063] In step S2, the raw materials are mixed by combining mechanical stirring and ultrasonic stirring to ensure uniform mixing, and the particle size of the mixed powder is 1-10 microns. The combination of mechanical stirring and ultrasonic stirring ensures the uniformity of the powder. The micron-level particle size helps to improve the density and uniformity of the magnetic core, thereby improving the magnetic properties.

[0064] The pressing and forming in step S3 adopts the cold isostatic pressing technology, and the cold isostatic pressing technology specifically includes:

[0065] S301, first, select appropriate high-purity powder materials, and mix and pre-treat them;

[0066] S302, loading the pretreated powder into a flexible mold;

[0067] S303, placing the mold filled with powder into a high-pressure container, and the high-pressure container is filled with fluid;

[0068] S304, gradually increasing the pressure of the fluid in the container to 200 MPa by means of a pump or other pressurizing equipment;

[0069] S305, after reaching the required pressure, maintain it for 30 minutes;

[0070] S306, after the pressing is completed, gradually reduce the pressure in the container until it returns to normal pressure, then remove the mold from the pressure container, carefully dismantle the mold, and take out the pressed blank;

[0071] S307, the pressed blank is further sintered;

[0072] The cold isostatic pressing technology allows the magnetic core to be evenly stressed during the pressing process to improve the density and uniformity of the magnetic core, significantly improving the density and structural uniformity of the magnetic core, thereby enhancing the mechanical strength and magnetic properties of the magnetic core.

[0073] In step S4, vacuum sintering is used to reduce the influence of impurities and improve the magnetic properties. The temperature is controlled at 800°C-1200°C for 2-4 hours. Vacuum sintering reduces the influence of impurities and improves the purity and magnetic properties of the magnetic core. Strict temperature and time control ensures the stability and consistency of the sintering process.

[0074] In step S5, cooling is performed by using a graded cooling technique and controlling the cooling rate to avoid the influence of thermal stress on the performance of the magnetic core. The graded cooling technique specifically includes:

[0075] S501, after sintering is completed, the material is in a high temperature state;

[0076] S502, after reaching the initial cooling temperature of 600°C, maintaining the material at this constant temperature for 1 hour;

[0077] S503, after the isothermal holding stage, starting to gradually reduce the temperature, by controlling the temperature of the cooling medium and the temperature of the cooling chamber, slowly reducing the temperature at a rate of 10°C / min;

[0078] S504, after the slow cooling stage, the material temperature is further reduced to close to the ambient temperature, and this stage is completed by natural cooling and air cooling;

[0079] By cooling fast first and then slowing down, internal stress can be further reduced and the stability of the magnetic core can be improved.

[0080] The performance test in step S6 includes the detection of magnetic permeability, coercive force, saturation flux density, and temperature stability parameters to ensure that the magnetic core meets the use requirements of the automobile charging pile. Through comprehensive performance testing, it is ensured that the various parameters of the magnetic core meet the use requirements of the automobile charging pile, the quality and consistency of the magnetic core are guaranteed, and the performance and efficiency of the charging pile are improved.

[0081] The outer end of the soft magnetic core is coated with a protective film using plasma spraying and chemical vapor deposition technology. The protective film is made of any one of aluminum oxide and silicon nitride. The protective film can effectively isolate the external environment, prevent moisture and oxygen from corroding the core material, and improve its corrosion resistance.

[0082] See also Figure 2-3The outer end of the protective film is fixedly connected with a plurality of uniformly separated composite particle balls, the composite particle ball comprises a wrapping ball film 1, the wrapping ball film 1 is fixedly connected to the outer end of the protective film, the wrapping ball film 1 is filled with a softening solidifying glue 2, the softening solidifying glue 2 is doped with heat-insulating particles 3, the wrapping ball film 1 is made of wax material, the softening solidifying glue 2 is made of thermoplastic polyurethane material, which has good elasticity, wear resistance and chemical resistance, it softens when heated, hardens again after cooling, and can be designed to have a certain moisture absorption capacity, and its hygroscopicity is enhanced by adding specific chemical components, so that it can absorb moisture while maintaining viscosity, and the heat-insulating particles 3 are made of aerogel material, and the aerogel is extremely It is composed of tiny nanopores and has extremely low thermal conductivity, so it can effectively insulate heat. The ball wrapping film 1 is melted by heat to expose the softened solidified glue 2, and the softened solidified glue 2 is softened by heat and spread out to increase the surface area and connect with the other multiple softened solidified glues 2. Then, the heat is insulated by the thermal insulation particles 3 to prevent heat loss, thereby improving the thermal stability of the magnetic core. The composite particle ball can effectively insulate heat and enhance the thermal stability of the magnetic core. The ball wrapping film is made of wax material, the softened solidified glue is made of thermoplastic polyurethane material, and the thermal insulation particles are made of aerogel material. Through the clever combination of these materials, the composite particle ball can soften and adhere when heated, thereby improving the thermal stability and heat loss resistance of the magnetic core.

[0083] See also Figure 4 The composite particle ball preparation method comprises the following steps:

[0084] ①, using hot-melt material to make the wrapped ball film 1 and reserving the injection hole, the wrapped ball film 1 is made of the existing spherical mold;

[0085] ②, the softened solidified glue 2 and the heat-insulating particles 3 are uniformly mixed and then injected into the wrapped ball film 1 and the holes are sealed to obtain a composite particle ball;

[0086] ③. Sprinkle the obtained composite particle balls evenly on the surface of the coating protective film before it solidifies.

[0087] Embodiment 2:

[0088] S1, select high-purity iron powder 75wt%, nickel powder 10wt%, cobalt powder 10wt%, and rare earth element 5wt% as raw materials;

[0089] S2, the raw materials selected in step S1 are mixed evenly according to proportion and nano-scale conductive particles are added, and mechanical stirring and ultrasonic stirring are combined to obtain a mixed powder with a particle size of 3 microns;

[0090] S3, placing the mixed powder in a flexible mold, pressing and molding by cold isostatic pressing technology, and uniformly pressurizing the fluid in the high-pressure container to obtain a magnetic core of a preliminary shape;

[0091] S4, sintering the pressed magnetic core in a high temperature furnace and adding a hydrogen reducing atmosphere, vacuum sintering at a temperature of 1000°C for 2 hours, and naturally cooling the sintered magnetic core to room temperature;

[0092] S5. The cooled magnetic core is processed by mechanical grinding and chemical polishing, and a graded cooling technology is used, including initial cooling, isothermal holding, slow cooling, and final cooling, to obtain a magnetic core of a desired size and shape;

[0093] S6. Conduct magnetic property tests on the prepared magnetic core, including magnetic permeability, coercive force, saturation flux density and temperature stability parameters.

[0094] Embodiment 3:

[0095] S1, select high-purity iron powder 65wt%, nickel powder 15wt%, cobalt powder 5wt%, and rare earth element 1wt% as raw materials;

[0096] S2, the raw materials selected in step S1 are mixed evenly according to proportion and nano-scale conductive particles are added, and mechanical stirring and ultrasonic stirring are combined to obtain a mixed powder with a particle size of 1 micron;

[0097] S3, placing the mixed powder in a flexible mold, pressing and molding by cold isostatic pressing technology, and uniformly pressurizing the fluid in the high-pressure container to obtain a magnetic core of a preliminary shape;

[0098] S4, sintering the pressed magnetic core in a high temperature furnace and adding a hydrogen reducing atmosphere, vacuum sintering at a temperature of 800°C for 4 hours, and naturally cooling the sintered magnetic core to room temperature;

[0099] S5. The cooled magnetic core is processed by mechanical grinding and chemical polishing, and a graded cooling technology is used, including initial cooling, isothermal holding, slow cooling, and final cooling, to obtain a magnetic core of a desired size and shape;

[0100] S6. Conduct magnetic property tests on the prepared magnetic core, including magnetic permeability, coercive force, saturation flux density and temperature stability parameters.

[0101] Comparison summary:

[0102] By comparing the test data of the three embodiments 1-3 with the prior art products, the magnetic permeability of all the embodiments is significantly higher than that of the prior art products, indicating that the new process materials are superior in magnetic properties. The coercive force of the embodiments is lower than that of the prior art products, showing the characteristics of being easier to magnetize and demagnetize, and are suitable for applications that require frequent switching of magnetic states. The saturation flux density of the embodiments is significantly higher than that of the prior art products, which means that they can operate at higher magnetic field intensities and are suitable for high magnetic field applications. In terms of temperature stability, the temperature change rate of the embodiments is small, showing the advantage of more stable performance at different temperatures. Although the new process materials have significant advantages in performance, their material cost and process complexity are also high, which may be due to the use of higher quality raw materials and more complex manufacturing processes.

[0103] It can be seen from the above technical solutions that the present invention has the following beneficial effects:

[0104] This solution uses high-purity iron powder, nickel powder, cobalt powder and rare earth elements to ensure high magnetic permeability and low coercive force of the magnetic core, and greatly improves the high-temperature stability and antioxidant properties of the magnetic core. Nano-scale conductive particles are added during the raw material mixing process to further optimize the electromagnetic properties of the magnetic core and improve the conductivity and environmental adaptability of the magnetic core. Mechanical stirring and ultrasonic stirring are combined to ensure the uniformity of the mixed powder and control the powder particle size within microns, which helps to improve the density and uniformity of the magnetic core, thereby optimizing the magnetic properties. Cold isostatic pressing technology is used to ensure that the magnetic core is evenly stressed during the pressing process, which significantly improves the density and structural uniformity of the magnetic core, and enhances its mechanical strength and magnetic properties. A hydrogen reducing atmosphere is added during the vacuum sintering process to reduce the impact of impurities, improve the purity and magnetic properties of the magnetic core, and ensure the stability and consistency of the sintering process. Graded cooling technology is used and the cooling rate is controlled. The cooling method of first fast and then slow is used to effectively avoid the impact of thermal stress on the performance of the magnetic core, further reduce internal stress, and improve the stability of the magnetic core. Mechanical grinding and chemical polishing improve the surface finish and dimensional accuracy of the magnetic core, ensuring that the final shape and size of the magnetic core meet the requirements. Comprehensive tests are carried out on the magnetic permeability, coercive force, saturation flux density and temperature stability parameters to ensure that the magnetic core meets the use requirements of the car charging pile, ensuring product quality and consistency. Plasma spraying and chemical vapor deposition technology are used to coat the outer end of the magnetic core with a protective film of aluminum oxide and silicon nitride materials to effectively isolate the external environment, prevent moisture and oxygen from corroding the magnetic core material, improve its corrosion resistance, and extend the service life of the magnetic core. Multiple composite particle balls are fixedly connected to the outer end of the protective film. The composite particle balls are composed of a wrapping ball film, a softening and solidifying glue, and thermal insulation particles, which can effectively isolate heat and enhance the thermal stability of the magnetic core. The wrapping ball film is made of wax material, the softening and solidifying glue is made of thermoplastic polyurethane material, and the thermal insulation particles are made of aerogel material. Through the clever combination of these materials, the composite particle balls can soften and adhere when heated, thereby improving the thermal stability and heat loss resistance of the magnetic core.

[0105] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and range of equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0106] In addition, it should be understood that although the present specification is described according to embodiments, not every embodiment contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation methods that those skilled in the art can understand.

Claims

1. A method for preparing a soft magnetic core for a car charging pile, characterized in that: The following steps are involved: S1. Select high-purity iron powder, nickel powder, cobalt powder, and a small amount of rare earth elements as raw materials; S2, mixing the raw materials selected in step S1 uniformly according to proportion and adding nano-scale conductive particles to obtain a mixed powder; S3, placing the mixed powder in a mold and pressing it under high pressure to obtain a magnetic core of a preliminary shape; S4, sintering the pressed magnetic core in a high temperature furnace and adding a hydrogen reducing atmosphere, and the sintered magnetic core is naturally cooled to room temperature; S5, mechanically grinding and chemically polishing the cooled magnetic core to obtain a magnetic core of a desired size and shape; S6. Conducting magnetic property testing on the prepared magnetic core; Wherein: the pressing and forming in step S3 adopts cold isostatic pressing technology, and the cold isostatic pressing technology specifically includes: S301, first, select appropriate high-purity powder materials, and mix and pre-treat them; S302, loading the pretreated powder into a flexible mold; S303, placing the mold filled with powder into a high-pressure container, and the high-pressure container is filled with fluid; S304, gradually increasing the pressure of the fluid in the container to 200 MPa by means of a pump or other pressurizing equipment; S305, after reaching the required pressure, maintain it for 30 minutes; S306, after the pressing is completed, gradually reduce the pressure in the container until it returns to normal pressure, then remove the mold from the pressure container, carefully dismantle the mold, and take out the pressed blank; S307, the pressed blank is further sintered.

2. The method for preparing a soft magnetic core for a car charging pile according to claim 1, characterized in that: The raw material ratio in step S1 is 65-75wt% of iron powder, 10-15wt% of nickel powder, 5-10wt% of cobalt powder, and 1-5wt% of rare earth elements.

3. The method for preparing a soft magnetic core for a car charging pile according to claim 1, characterized in that: In step S2, the raw materials are mixed by combining mechanical stirring and ultrasonic stirring, and the particle size of the mixed powder is 1-10 microns.

4. The method for preparing a soft magnetic core for a car charging pile according to claim 1, characterized in that: The sintering in step S4 is performed by vacuum sintering, and the temperature is controlled at 800° C.-1200° C. for 2-4 hours.

5. The method for preparing a soft magnetic core for a car charging pile according to claim 1, characterized in that: In step S5, cooling is performed by using a graded cooling technique and controlling the cooling rate. The graded cooling technique specifically includes: S501, after sintering is completed, the material is in a high temperature state; S502, after reaching the initial cooling temperature of 600°C, maintaining the material at this constant temperature for 1 hour; S503, after the isothermal holding stage, starting to gradually reduce the temperature, by controlling the temperature of the cooling medium and the temperature of the cooling chamber, slowly reducing the temperature at a rate of 10°C / min; S504, after the slow cooling stage, the material temperature is further reduced to close to the ambient temperature. This stage is completed by natural cooling and air cooling.

6. The method for preparing a soft magnetic core for a car charging pile according to claim 1, characterized in that: The performance test in step S6 includes the test of magnetic permeability, coercive force, saturation magnetic flux density, and temperature stability parameters.

7. The method for preparing a soft magnetic core for a car charging pile according to claim 1, characterized in that: The outer end of the soft magnetic core is coated with a protective film, and the protective film is made of any one of aluminum oxide and silicon nitride.

8. The method for preparing a soft magnetic core for a car charging pile according to claim 7, characterized in that: The outer end of the protective film is fixedly connected to a plurality of uniformly distributed composite particle balls, the composite particle balls comprising a wrapping ball film (1), the wrapping ball film (1) is fixedly connected to the outer end of the protective film, the wrapping ball film (1) is filled with a softening solidifying glue (2), and the softening solidifying glue (2) is doped with heat insulating particles (3) in the middle.

9. The method for preparing a soft magnetic core for a car charging pile according to claim 8, characterized in that: The composite particle ball preparation method comprises the following steps: ①, using hot-melt material to make a ball wrapping membrane (1) and reserving a material injection hole; ②, uniformly mixing the softened solidified glue (2) and the heat insulating particles (3), injecting them into the ball wrapping film (1) and sealing the holes to obtain a composite particle ball; ③. Sprinkle the obtained composite particle balls evenly on the surface of the coating protective film before it solidifies.

Citation Information

Patent Citations

  • Magnetic powder core material with stable magnetic permeability and low loss and preparation method thereof

    CN108335820A

  • Soft magnetic alloy powder, dust core and magnetic component

    CN110246650A